Voluntad Procreacional (Procreational Will) - Aníbal Guzmán Ávalos; María del Carmen Valdés Martínez (Oñati Socio-Legal Series)
The use of assisted reproduction techniques in Mexico and world wide require the consent of the users as an legal essential element of this legal figure; the current essay focus on the analysis of the procreational will as an element of this new filiation mode, in the context of the different normative hypothesis provided by the Mexican law.